Correlations between factor of safety with distributed load and crest length – Zariwam landslide as case study - Muhammad Israr Khan (Geology, Ecology, and Landscapes)
This paper examines the impact on Factor of Safety (FS) value due to the variation in distributed load (LD), Crest length (CL), shear strength (τ), and shear stress (σ) both in seismic and non-seismic conditions. The main purpose of this paper is to develop correlations between these parameters, which can be used in any slope stability analysis design project. Forty number of analyses are performed by considering different soil material properties. Slope stability analysis is performed using Slide software and correlations are developed using Statistical Package for Social Sciences (SPSS) software as well as with the help of Microsoft Excel. The analysis results indicate that the seismic slope stability analysis gives optimum value for slope FS and therefore it is highly recommended to perform and give preference to seismic slope stability analysis of any soil slope to compute and recommend FS value. The main novelty of this paper are the eight new correlations. These correlations can be used in slope stability projects like earthfill dams design, embankments, or any slope design project or case study to know about the slope factor of safety in detail.